Optimization of thickness of GAGG scintillator for detecting an alpha particle emitter in a field of high beta and gamma background. (May 2018) - Morishita, Yuki; Yamamoto, Seiichi; Izaki, Kenji; Kaneko, Junichi H.; Hoshi, Katsuya; Torii, Tatsuo
Abstract: At the site of the Fukushima Daiichi nuclear power plant (FDNPP), there is a large quantity of beta and gamma emitters such as 90 Sr and 137 Cs. Moreover, radon (Rn) progeny, which are naturally occurring radionuclides, exist and emit alpha and beta particles. To detect plutonium isotopes ( 238 Pu, 239 Pu, and 240 Pu) in a field of high beta and gamma background, an alpha particle detector with low beta- and gamma-ray sensitivity and good energy resolution for an alpha particle is required to distinguish plutonium isotopes from Rn progeny. Previously, we developed an alpha particle imaging detector by combining a 0.1-mm-thick gadolinium aluminum gallium garnet (GAGG) scintillator with a silicon photomultiplier (SiPM). However, this detector was sensitive to environmental gamma and beta rays. In this study, we optimized the thickness of the GAGG scintillator for alpha particle detection in a field of high beta and gamma background. We prepared three GAGG scintillators with thicknesses of 0.05 mm, 0.07 mm, and 0.1 mm. Each of the GAGG scintillators was coupled optically to the SiPM array, which was used as the photodetector. Alpha, beta, and gamma rays were irradiated onto the developed alpha particle detector, and their spectra were obtained. The energy resolution of the 0.05-mm-thick GAGG for 5.5-MeV alpha particles (∼11.6% full width at half maximum [FWHM]) was the best among the three GAGG scintillators. All GAGG scintillators used in this study were not sensitive to gamma rays with a dose rate of 1 mSv/h. The beta particle count above the lower level discriminator (LLD) decreased because the scintillator was thinner, and the beta count of the 0.05-mm-thick GAGG was only 1/100 that of the 0.1-mm-thick GAGG. Because the alpha particle detector with the 0.05-mm-thick GAGG scintillator had low beta and gamma-ray sensitivity and good energy resolution for alpha particles, it is promising from the viewpoint of detecting plutonium contamination in a field with high beta and gamma background, such as the FDNPP site. Highlights: Three GAGG scintillators with different thicknesses for detecting alpha particle were compared for in a field of high beta and gamma background. The energy resolution of the 0.05-mm-thick GAGG for alpha particles was the best (∼11.6% FWHM). All GAGG scintillators were not sensitive to gamma rays with a dose rate of 1 mSv/h. The beta count of the 0.05-mm-thick GAGG was only 1/100 that of the 0.1-mm-thick GAGG. The 0.05-mm-thick GAGG scintillator is promising for detecting alpha emitter such as plutonium in a field with high beta and gamma background.